Simultaneous Detection and Repair of Wetting Defects in Superhydrophobic Coatings via Cassie–Wenzel Transitions of Liquid Marbles. (8th April 2019) - Tenjimbayashi, Mizuki; Samitsu, Sadaki; Naito, Masanobu
Abstract: Superhydrophobic materials that prevent unwanted liquid adhesion can easily lose this property because of limited mechanical durability despite topological/chemical control and/or robust material selection. Here, long‐lasting superhydrophobic coatings with a system to effectively detect and repair damaged areas with "liquid marble, " a droplet covered with hydrophobic nanoparticles, are reported. The particles prevent direct contact between the droplet and the substrate (Cassie state). However, they can adhere to the non‐superhydrophobic damaged area in response to the substrate wettability via an external force or an increase in liquid volume via penetration of the outer nanoparticle layer (Wenzel state). This Cassie–Wenzel transition thus induces self‐assembly of the nanoparticles onto the non‐superhydrophobic area in response to the wettability, restoring superhydrophobicity. Abstract : Simultaneous detection and repair of wetting defects for superhydrophobic coatings is realized by the wetting transition of liquid marbles. Under pressure the liquid marbles transition their wetting state from the Cassie to Wenzel state in response to wetting defects and repair their original wettability, which contributes to the design of long‐term stable superhydrophobic coatings.